Performance and reference intervals of thrombin generation test: results from the Brazilian longitudinal study of adult health (ELSA-Brasil). A cross-sectional study - Rios, Danyelle Romana Alves; Barreto, Sandhi Maria; Ferreira, Letícia Gonçalves Resende; Batista, Thaís Resende; Silva, Ana Paula Ferreira; Oliveira Júnior, Wander Valadares de; Maluf, Chams Bicalho; Carvalho, Maria das Graças; Figueiredo, Roberta Carvalho (São Paulo Medical Journal, 2022)
BACKGROUND: The thrombin generation test (TGT) has shown promise for investigation of hemorrhagic and thrombotic diseases. However, despite its potential, it still needs standardization. Moreover, few studies have established reference values for TGT parameters. In Brazil, these values have not yet been established. OBJECTIVE: To determine TGT performance and reference intervals for TGT parameters in healthy individuals. DESIGN AND SETTING: Cross-sectional study conducted among participants in the Brazilian Longitudinal Study of Adult Health (Estudo Longitudinal de Saúde do Adulto, ELSA-Brasil). METHODS: The reference sample consisted of 620 healthy individuals. The calibrated automated thrombogram (CAT) method, under low and high tissue factor (TF) conditions, was used to assess thrombin generation. Test performance was analyzed using intra and interassay coefficients of variation (CV) and reference intervals were calculated using the nonparametric method proposed by the international Federation of Clinical Chemistry and the Clinical and Laboratory Standards Institute. RESULTS: The intraassay CV ranged from 1.4% to 2.2% and the interassay CV, 6.8% to 14.7%. The reference intervals for TGT parameters under low and high TF conditions were, respectively: lagtime: 3.0-10.3 and 1.4-3.7 min; endogenous thrombin potential (ETP): 1134.6-2517.9 and 1413.6-2658.0 nM.min; normalized ETP: 0.6-1.3 and 0.7-1.4; peak: 103.2-397.7 and 256.4-479.0 nM; normalized peak: 0.3-1.3 and 0.7-1.2; and time-to-peak: 5.6-16.0 and 3.4-6.7 min. These parameters were categorized relative to sex. CONCLUSION: TGT performance was adequate and the proposed reference intervals were similar to those of other studies. Our findings may be useful for consolidating the TGT, through contributing to its standardization and validation.